КУЛЬТУРА МОВИ ВИКЛАДАЧА В СУЧАСНІЙ ПЕДАГОГІЧНІЙ МАЙСТЕРНОСТІ: СОЦІОЛІНГВІСТИЧНИЙ АСПЕКТ - Оксана Назаренко (Linguarum Universe, 2025)
This article examines the teacher's language culture in professional communication within the framework of modern pedagogical mastery, employing a sociolinguistic experiment and a questionnaire. The definitions of the concepts of communicative competence, language competence, and language personality are provided in detail. The main features of the teacher's language culture are considered, namely: correctness, accuracy, meaningfulness, logic, richness, relevance, and expressiveness. The most typical language problems in learners' communication are characterized, with the aim of preventing them in future pedagogical practice. Such lexical errors include: unmotivated use of Russian vocabulary, particularly calquing and surzhyk; use of repetition (tautology), pleonasm, and verbosity; inappropriate use of paronyms; duplication of cognate words; and excessive use of Anglicisms, for which Ukrainian equivalents were selected. The main forms of self-improvement and language culture improvement for future specialists are formulated. Attention is drawn to the linguocultural context of developing a teacher's language competence, its influence on shaping a harmoniously developed personality of the learner, fostering dialogic interaction, and organizing the educational process. It is proven that a teacher's language culture is an integral part of modern pedagogical mastery; it should form respect for the native language as well as for other languages and cultures within the context of a multicultural educational space in future pedagogical practice.